The thing, the book : a monument to the book as object. - Herschend, Jonn; Rogan, Will (San Francisco : Chronicle Books, 2014)
Featuring: Gwen Allen - Tauba Auerbach - John Baldessari - Martin Creed - Mark Dion - Anthony Discenza - Kota Ezawa - Harrell Fletcher - Ryan Gander - Sam Green - Jonn Herschend & Will Rogan - Matthew Higgs - Andrew Hultkrans - Chris Johanson - Miranda July - Starlee Kine - Andrew Leland - Jonathan Lethem - MacFadden & Thorpe - Mike Mills - Rick Moody - Dave Muller - Laurel Nakadate - Tucker Nichols - Trevor Paglen - Lucy Pullen - Ed Ruscha - Leslie Shows - David Shrigley - Molly Springfield - Sara VanDerBeek - Anne Walsh - Lawrence Wiener - Richard Wentworth
boek